Translating παρθένοσ in 1Cor. 7:25-38 (Hekima Review, 2016)
This paper aims at showing that Bible translators would satisfactorily over-come the challenges posed by the inadequate interpretations of παρθένος in 1 Cor 7:25-38 if they could take into consideration the findings of Chrys Caragounis. These find-ings – based on historical-critical research - include among other things a triple meaning of παρθένος (young virgin woman, young virgin man and the state of virginity), a preference for alternative reading γαμείτω (imperative singular) instead of the plural form γαμείτωσαν, and an interpretation of ὑπέρακμοςin the sense of sexual urges in place of flower of age. These findings are strengthened by some inputs from intercultural analysis, highlighting that variants γαμείτωσαν and γαμείτω can be understood as parallel readings that point to the diversity in the ways of interpreting the very issue during the times of the original biblical cultures; and secondly it has also elucidated the importance of παρθένος phenomenon in Church cultures